PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL PRAKTEK KERJA INDUSTRI SISWA KELAS XII SMK NEGERI 1 LINTAU BUO - Muhammad Irhas Athariq; Totoh Andayono, ST, MT (Universitas Negeri Padang, 2019)
Abstract―Practice of Industrial or commonly referred to as Prakerin is a realization of the part of education in Vocational High School (SMK) by providing students directly to enter the Business and Industrial World. The reason is, students must be equipped with soft skills and hard skills, one of the soft skills that students must possess is to be able to problems solve which can be seen from the Emotional Intelligence of the student in order to support the Prakerin Results or the values obtained. Therefore, this study aims to find out how much influence emotional intelligence has on the results of industrial practice or prakerin of students at SMK 1 Lintau Buo.This type of research is a correlation research with a population of 250 students with a sample of 154 students, taken using Proportional Random Sampling technique. The type of data used is primary and secondary data. Primary data is obtained through questionnaires distributed to students, while secondary data is data obtained from Public Relations of SMK 1 Lintau Buo. Data analysis techniques used are: 1) Descriptive analysis, 2) Test requirements analysis, which consists of normality test and linearity test to prove that the distribution of data comes from samples that are normally and linearly distributed, and 3) Hypothesis Test. The results of this study can be concluded that there is an influence between emotional intelligence on the results of the practicum of students of SMK 1 Lintau Buo with the correlation coefficient number of 0.193 and the percentage contribution to learning outcomes of 3.72%.Keywords: Emotional Intelligence, Prakerin Results